2006
DOI: 10.1182/blood.v108.11.3061.3061
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Chemotherapy Followed by Autologous Hematopoietic Stem Cell Transplantation (AHSCT) for Lymphocyte Predominant Hodgkin’s Disease.

Abstract: Lymphocyte Predominant Hodgkin’s Disease (LPHD) is a B-cell lymphoma that may require different treatment and may have a different natural history than classical Hodgkin’s disease. Although AHSCT is accepted therapy for patients with relapsed and refractory classical Hodgkin’s disease, there is little information regarding transplantation for LPHD. We performed a retrospective analysis of 19 patients who were treated with AHSCT for relapsed or refractory LPHD at the University of Nebraska Medical Center betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In contrast, the role of auto‐SCT in NLPHL is not well defined. To date, only a few series on NLPHL autografts have been reported, all of them limited by small patient numbers precluding valid conclusions . Here, we report the largest cohort of patients with NLPHL who underwent auto‐SCT for relapsed or refractory disease, after responding to salvage therapy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, the role of auto‐SCT in NLPHL is not well defined. To date, only a few series on NLPHL autografts have been reported, all of them limited by small patient numbers precluding valid conclusions . Here, we report the largest cohort of patients with NLPHL who underwent auto‐SCT for relapsed or refractory disease, after responding to salvage therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Akhtar et al reported 17 patients (including 4 transformed to high‐grade lymphoma) with 5‐year OS and PFS of 76% and 94% . Another small study on 19 patients with NLPHL, available only in abstract form, reported slightly inferior 5‐year estimates (OS 56%, PFS 40%) . A few additional very small anecdotal case series have been reported but given the small number of patients per case series, firm conclusions are difficult .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, в исследовании, включающем 19 больных за период с 1987 по 2002 г. 5-летняя ОВ составила 53% и выживаемость без прогрессии -39% [23]. В другом исследовании, включавшем 88 больных НЛХЛП, из которых 8 после первого рецидива и более получили высокодозную ХТ с трансплантацией ауто-СКК, медиана продолжительности жизни в отсутствие неэффективности лечения составила 39,2 мес, при этом вновь возникло 5 рецидивов.…”
Section: таблица 1 различие клеток березовского-штернберга и клеток unclassified
“…One study retrospectively analyzing the use of high‐dose chemotherapy followed by ASCT in relapsed NLPHL included 19 patients that had been transplanted between 1987 and 2002. At 5 years, PFS and OS rates were 39% and 53%, respectively, and thus not very promising given the excellent long‐term survival rates reported for NLPHL even after relapse . Additional data on the value of high‐dose chemotherapy followed by ASCT in patients with relapsed NLPHL came from the UK.…”
Section: Introductionmentioning
confidence: 99%